Comparative study of range of motion and anterior knee pain in parapatellar versus trans patellar approach in tibia nailing - Deokar, Nikhil Pralhad; Gaonkar, Kiran L.; Daruwala, Siddharth; Jagdale, Anshuraj (International Journal of Research in Orthopaedics, 2022)
Background: Tibial shaft fractures are common traumatic fractures especially in road traffic accidents. Intramedullary interlocking nailing is considered treatment of choice tibial diaphyseal fractures, minimizing soft tissue injury and permitting early weight bearing and fracture healing. Anterior knee pain and reduced range of motion are some common complications that patients have to face in post-operative period. Methods: The 60 patients of both sex with traumatic diaphyseal tibial shaft fractures were included in this study out of which 30 were operated with interlocking tibia nailing with trans patellar (tendon splitting) approach while 30 were operated with medial parapatellar approach for tibia nail insertion. Range of motion at knee joint (in degrees) and anterior knee pain (on visual analogue scale) was evaluated on post-operative day 1, 2 weeks, 1 month, 3-month post operatively and compared for both groups. Results: Mean anterior knee pain was significantly lower in parapatellar approach group at 2 weeks, 1 month and 3 months while there was no significant diﬀerence on post-operative day 1. Mean range of motion at knee joint was more in parapatellar approach group on post-operative day 1 and 2 weeks while there was no significant diﬀerence in range of motion after 2 weeks. Conclusions: In our study medial parapatellar approach is superior than tendon splitting approach with comparatively greater range of motion and lesser anterior knee pain. Thus, medial parapatellar approach should be encouraged for interlocking tibia nailing.